A naphthalimide-aminal-based pH-sensitive fluorescent donor for lysosome-targeted formaldehyde release and fluorescence turn-on readout. Issue 49 (30th May 2019) - Xu, Hang; Ma, Shengnan; Liu, Qianqian; Huang, Lixian; Wu, Peimin; Liu, Xiaolin; Huang, Yali; Wang, Xiaolei; Xu, Huan; Lou, Kaiyan; Wang, Wei
Abstract : NAP-FAD-1 is a pH-sensitive smart formaldehyde donor with fluorescence turn-on readout for facile tracking and quantification of formaldehyde release. Abstract : A naphthalimide-aminal-based fluorescent donor (NAP-FAD-1 ) is a pH-sensitive smart donor, which features accelerated FA release at pH 5.0 compared to that at pH 7.4 and fluorescence turn-on readout for facile tracking and quantification of FA release. Confocal imaging studies of HeLa cells co-incubated with Lyso-Tracker Red suggested that its FA release is lysosome-targeted.